CH4 flux and gas exchange from Almbergasjön, 2017-07-10–2022-10-03 - Abisko Scientific Research Station (Swedish Polar Research Secretariat, 2026)
As part of the SITES Water GHG chamber program, floating chambers were placed on surface water at various locations in the lake to capture CH4 flux. Data contains surface water dissolved CH4 concentration, CH4 flux and associated gas exchange velocity [k].
Abisko Scientific Research Station (2026). CH4 flux and gas exchange from Almbergasjön, 2017-07-10–2022-10-03 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/2plf2k6BwxvvPutoOiywtH0a
Keywords: SITES; Time instant; Time instant; Latitude; Latitude; Longitude; Longitude; Water depth; Water depth; Water temperature; Water temperature; Dissolved methane; Dissolved methane; Gas exchange velocity of methane; Gas exchange velocity of methane; Methane flux; Methane flux; Quality flag; Quality flag; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap